P-BN02 Experience in Transitioning From Laparoscopic to Robotic-Assisted ParaEsophageal Hernia Repair - A Single Centre Experience. (16th December 2021) - Azzawi, Mohammed Al; Ismael, Ghazi; Bolger, Jarlath; Robb, William
Abstract: Background: Paraesophageal hernias (PEH) constitute only 5% of hiatal hernias. They may give rise to significant post-prandial symptoms, acute episodes of obstruction or gastric ischaemia and patient mortality.  Surgical repair of symptomatic PEHs is the current standard of care. This study explores our centre's experience with the introduction of Robotic Assisted PEH (RA-PEH) repair in comparison to our longer established technique of laparoscopic repair. Methods: Retrospective review of all laparoscopic and robotic PEH repair using the DaVinci Xi between January 2017 and May 2020 by a single surgeon in 2 institutions. A total of 27 cases were included in our review. An analysis of patient demographics, operative time and approach, morbidity and mortality was performed.  Results: Sixteen patients underwent laparoscopic repairs and 11 underwent elective robotic repair. Fundoplication was performed in both groups while mesh repair was used in 18% of the laparoscopy group. Type IV hiatal hernia was found in 50% and 37% in the laparoscopy and RA-PEH groups, respectively. Mean operative time was 144 minutes in the laparoscopy group and 153 minutes for RA-PE (p = 0.07). Median length of stay was 2 days for both groups (p = 0.18). Post-operative morbidity occurred in 37% and 9% in the laparoscopy and RA-PEH groups respectively (p = 0.18). There was 1 case of acute post-operative recurrence and re-operation in the laparoscopy group. Conclusions: Minimally invasive surgery is the standard of treatment in PEH repair. The robotic technique is a safe and effective approach when compared to the standard laparoscopic repair. It may have an advantage in reducing reliance on the necessity of having experienced assistance in the operating theatre without utilising more theatre time.